2018
DOI: 10.1186/s13326-017-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the challenges of matching biomedical ontologies

Abstract: BackgroundBiomedical ontologies pose several challenges to ontology matching due both to the complexity of the biomedical domain and to the characteristics of the ontologies themselves. The biomedical tracks in the Ontology Matching Evaluation Initiative (OAEI) have spurred the development of matching systems able to tackle these challenges, and benchmarked their general performance. In this study, we dissect the strategies employed by matching systems to tackle the challenges of matching biomedical ontologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Faria et al [8] identified the different challenges to align large biomedical ontologies. Ensuring good quality alignments while aligning these ontologies is challenging.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Faria et al [8] identified the different challenges to align large biomedical ontologies. Ensuring good quality alignments while aligning these ontologies is challenging.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, the class UBERON 0001275 ("pubis") of Uberon references the FMA class 16595 ("pubis") and NCI class C33423 ("pubic bone"). Therefore, the later entities construct a positive sample of a local training set [8]. Resampling of the Local Training Data: The training set is not balanced since the number of the negative samples M is higher than the number of positive samples N .…”
Section: Local Matching Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by appropriately leveraging ontology mapping algorithms mentioned above for biomedical concepts, we would be able to discover new relations among biomedical concepts, such as those of equivalent and overlapping relations, which could not be identified using only string comparison techniques, such as the LOOM. For example, there is an ontology mapping system "AgreementMaker-Light (AML) [52]," which implements some matching algorithms: (1) "The Lex-icalMatcher" to find literal full name matches between the lexicon entries of two ontologies, (2) "The ThesaurusMatcher," to find literal full name matches involving synonyms inferred from an automatically generated thesaurus, and (3) "The XRefMatcher," which uses cross-reference information among data sources. In the AML's matching tasks using anatomy, phenotype, and disease datasets, they have demonstrated that not only the precision rate but also recall rate and F-measure were improved, simply by optimizing the algorithm parameters or combining some algorithms [52].…”
Section: Inference Of Chemical Compounds For Functions/roles/applicatmentioning
confidence: 99%
“…In recent years, various biomedical ontologies, such as FMA (Detwiler, Mejino, & Brinkley, 2016) and SNOMED-CT (Filice & Kahn, 2019), have been widely used in the life science domain (Faria et al, 2018). However, existing biomedical ontologies that cover overlapping domains are mostly developed independently, and the different ways of defining the same biomedical concept yield heterogeneous problems among biomedical ontologies, which hampers their inter-operability.…”
Section: Introductionmentioning
confidence: 99%